2015
DOI: 10.1093/humrep/dev296
|View full text |Cite
|
Sign up to set email alerts
|

Timing of human preimplantation embryonic development is confounded by embryo origin

Abstract: STUDY QUESTIONTo what extent do patient- and treatment-related factors explain the variation in morphokinetic parameters proposed as embryo viability markers?SUMMARY ANSWERUp to 31% of the observed variation in timing of embryo development can be explained by embryo origin, but no single factor elicits a systematic influence.WHAT IS KNOWN ALREADYSeveral studies report that culture conditions, patient characteristics and treatment influence timing of embryo development, which have promoted the perception that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 37 publications
(53 reference statements)
1
58
0
Order By: Relevance
“…Previous reports have shown that early‐cleavage embryos had strong developmental potential . Some studies classified all embryos into “early‐cleavage” and “non‐early‐cleavage” groups and compared them .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have shown that early‐cleavage embryos had strong developmental potential . Some studies classified all embryos into “early‐cleavage” and “non‐early‐cleavage” groups and compared them .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies classified all embryos into “early‐cleavage” and “non‐early‐cleavage” groups and compared them . Other studies also grouped the embryos into those that ultimately resulted in pregnancy and those that did not . In contrast, this study compared the embryos that were retrieved from a single oocyte retrieval cycle and measured the synchrony of the first division, thereby predicting the subsequent embryo development more accurately than the retardation time until first division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They depend on many factors that influence embryo development. Kirkegaard et al demonstrated that up to 31% of variation in timing of the events in embryo development can be explained by the origin of the embryo, including the patient-related and treatment-related factors [39]. Because of these limitations, as well as the small study size, timing of the events was not the primary study focus, but, rather, the occurrence of the cleavage abnormalities was.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' age and dose of FSH have a positive correlation with delayed blastocyst development. It is also shown that embryos fertilized by ICSI have a signiicant faster irst cleavage division than IVF originate embryos [49].…”
Section: Diferent Studies Based On Time-lapse Observationmentioning
confidence: 99%